2009
DOI: 10.1029/2009gl037274
|View full text |Cite
|
Sign up to set email alerts
|

Winter Northern Hemisphere weather patterns remember summer Arctic sea‐ice extent

Abstract: [1] The dramatic decline in Arctic summer sea-ice cover is a compelling indicator of change in the global climate system and has been attributed to a combination of natural and anthropogenic effects. Through its role in regulating the exchange of energy between the ocean and atmosphere, ice loss is anticipated to influence atmospheric circulation and weather patterns. By combining satellite measurements of sea-ice extent and conventional atmospheric observations, we find that varying summer ice conditions are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

21
316
5
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 353 publications
(345 citation statements)
references
References 24 publications
21
316
5
3
Order By: Relevance
“…[7] Evidence supporting the first effect -zonal wind reduction -was identified in a previous study by Francis et al [2009], who found that poleward thickness gradients were weaker over the N. Atlantic and N. Pacific in summers with less sea ice than normal, and that the weakening persisted well into the following spring. This tendency is also clearly evident over the present study region, as shown in the time series of 1000-500 hPa thickness differences between a high-latitude region (80-60 N) and low-latitude region (50-30 N) for each season (Figure 3, left).…”
Section: Analysis and Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…[7] Evidence supporting the first effect -zonal wind reduction -was identified in a previous study by Francis et al [2009], who found that poleward thickness gradients were weaker over the N. Atlantic and N. Pacific in summers with less sea ice than normal, and that the weakening persisted well into the following spring. This tendency is also clearly evident over the present study region, as shown in the time series of 1000-500 hPa thickness differences between a high-latitude region (80-60 N) and low-latitude region (50-30 N) for each season (Figure 3, left).…”
Section: Analysis and Resultsmentioning
confidence: 85%
“…Both observational and modeling studies have identified a variety of large-scale changes in the atmospheric circulation associated with sea-ice loss and earlier snow melt, which in turn affect precipitation, seasonal temperatures, storm tracks, and surface winds in mid-latitudes [e.g., Budikova, 2009;Honda et al, 2009;Francis et al, 2009;Overland and Wang, 2010;Petoukhov and Semenov, 2010;Deser et al, 2010;Alexander et al, 2010;Jaiser et al, 2012;Blüthgen et al, 2012]. While it is understood that greenhouse-gas-induced tropospheric warming will cause an increase in atmospheric water content that is expected to fuel stronger storms and flooding [Meehl et al, 2007], individual extreme weather events typically have a dynamical origin.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have linked sea ice loss to atmospheric warming in surrounding areas during other times of the year as well (Comiso et al, 2002;Hanna et al, 2004;Bhatt et al, 2010;Serreze et al, 2011). Sea ice loss is additionally tied to increased tropospheric moisture, precipitation, cloud cover, surface temperature, and decreased static stability (Deser et al, 2000;Rinke et al, 2006;Francis et al, 2009;Serreze et al, 2009;Kay et al, 2011;Screen and Simmonds, 2010;Stroeve et al, 2011;Overland and Wang, 2010;Cassano et al, 2014). Water vapor or moisture increases surface melting through its role in cloud formation and, as a greenhouse gas, results in increased downward longwave radiation and precipitation (Bennartz et al, 2013;Doyle et al, 2015;van Tricht et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies argued that the negative Arctic Oscillation (AO) resembling pattern in autumn can persist into winter (Francis et al 2009;Liu et al 2012;Li and Wang 2013b) whereas some other studies suggested that the autumn atmospheric response cannot persist into the mid-late winter (e.g., Blüthgen et al 2012;Screen et al 2013). Furthermore, Screen et al (2014) investigated the winter atmospheric response to the autumn Arctic sea-ice concentration (SIC) trend from 1979 to 2009 using two models and did not find the negative AO or NAO pattern.…”
Section: Introductionmentioning
confidence: 99%
“…The warmer ocean associated with the autumn sea-ice reduction can transfer more heat to the atmosphere (Blüthgen et al 2012), cause the low-troposphere warming (Kumar et al 2010;Blüthgen et al 2012;Screen et al 2014), moistening (Liu et al 2012;Screen et al 2013) and the changes in sea level pressure (SLP) over the Arctic (Screen et al 2014). The neutral or negative North Atlantic Oscillation (NAO) pattern can appear simultaneously in response to the summer-autumn sea-ice reduction (Francis et al 2009;Screen et al 2013;Walsh 2014).…”
Section: Introductionmentioning
confidence: 99%